Analisis Prospek Ekspor Karet Indonesia Ke Jepang - Silvia Atika; Syaad Afifuddin S (Ekonomi dan Keuangan, 2015)
The main point of this research is to analyze how Indonesian rubber export prospect to Japan dan factors that affect it. Where observed factors in this research are Indonesian rubber export volume to Japan, Indonesia rubber production, International rubber price, exchange rate dan Japan GDP. For analyze, the research use time series data from 1990-2013. The research model use econometric model. Analysis method use forecasting and Ordinary Least Square (OLS) Linear Regression. Result of this research show that Indonesian rubber export volume variable to Japan will increase every year in the future. Rubber production variable has positive relationship and significant towards Indonesian rubber export to Japan. International rubber price variable has negative relationship and insignificant towards Indonesian rubber volume export to Japan. Exchange rate variable has positive relationship and insignificant towards Indonesian rubber export volume to Japan. Japan GDP variable has negative relationship and insignificant towards Indonesia rubber export volume to Japan.Keywords: prospect, production, exchange rate, GDP, and rubber export